Tourism and visual culture. (CABI, 2010)
This second volume examines detailed methodological examples of visual concepts and their use and value in advancing knowledge and understanding of tourism beyond business and economics. The 17 chapters that make up this book can be divided into four separate but interconnected methodological categories: semiotics/symbolism; visual sociology/photo-elicitation; image analysis for destinations and marketing; and visual ethnography.